On the explicit asymptotic symmetry breaking of $$sl(3,\mathbb {R})$$ s l ( 3 , R ) Jackiw–Teitelboim gravity - H. T. Özer; Aytül Filiz (European Physical Journal C: Particles and Fields)
Abstract This study investigates the asymptotic symmetry algebras (ASA) of Jackiw–Teitelboim (JT) gravity within the framework of $$\mathfrak {sl}(3,\mathbb {R})$$ sl ( 3 , R ) symmetry. By explicitly constructing this algebra, we explore how the presence of the dilaton field influences the structure of asymptotic symmetries and symmetry breaking mechanisms at the AdS $$_2$$ 2 boundary. For the $$\mathfrak {sl}(3,\mathbb {R})$$ sl ( 3 , R ) model, the dilaton field preserves a subset of the complete $$W_3$$ W 3 -symmetry, restricting the algebra to $$\mathfrak {sl}(3,\mathbb {R})$$ sl ( 3 , R ) . These results provide deeper insights into the role of dilaton dynamics in holographic dualities, with implications for the thermodynamics and geometry of AdS $$_2$$ 2 . The findings pave the way for systematically exploring extended gauge symmetries in two-dimensional gravity and their relevance to higher-rank Lie algebras.